2009
DOI: 10.1007/s00417-009-1247-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of bevacizumab and triamcinolone acetonide at the end of vitrectomy for diabetic vitreous hemorrhage: a comparative study

Abstract: IVB and IVT injection at the end of diabetic vitrectomy is a useful adjunctive therapy for reducing early postoperative VH compared to the control group. IVB injection does not have a risk of a temporary rise of IOP, which the IVT group has.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…9,12 IVB after a vitrectomy also appears safe and effective for reducing postoperative VH, albeit without the benefit on final visual acuity. 21,22 In a randomized clinical trial, 25.7% of patients avoided the need for vitrectomy after IVB injection. 23 Although PRP is the principal therapy for PDR, substantial regression of NV may take weeks after completion of laser treatment, and it is not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 IVB after a vitrectomy also appears safe and effective for reducing postoperative VH, albeit without the benefit on final visual acuity. 21,22 In a randomized clinical trial, 25.7% of patients avoided the need for vitrectomy after IVB injection. 23 Although PRP is the principal therapy for PDR, substantial regression of NV may take weeks after completion of laser treatment, and it is not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively fewer studies have investigated the use of intravitreal anti-VEGF agents at the end of surgery; unfortunately, such studies yielded controversial findings. Some of these studies [9][10][11] reported that the use of anti-VEGF agents could significantly reduce the incidence of postoperative VH. Others, however, suggested that intravitreal anti-VEGF had no beneficial effect upon the incidence of postoperative VH when injected at the end of surgery [12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of such procedures remain controversial. Some authors have reported that when injected intraoperatively, anti-VEGF drugs could result in a reduction in the incidence of early recurrent VH and quicker absorption of recurrent VH [9][10][11]. Other studies, have reported the opposite effects [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…23 Some investigators have suggested the use of bevacizumab at the end of operation to reduce postoperative hemorrhage induced by early growth of neovascularization. 24,25 We injected 0.05 mg of bevasizumab before silicone oil infusion in an attempt to inhibit early postoperative neovascularization. The exact effect of the treatment in a silicone oil-filled eye remains to be studied.…”
Section: Discussionmentioning
confidence: 99%